Information provided for ecological quality management of production on microeconomic level under conditions of sustainable development - Zamula I.V.; Travin V.V.,; Prumak T.S. (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
Nowadays, economic development is characterized by increasing of contradictions between ecological and economic systems. As a result, the necessity of unity achievement is growing in the existence of ecological and economic values as one of the main conditions of the concept of sustainable development. For this purpose it is important to implement and create an ecological and economic management system at the enterprise to ensure ecological and economic efficiency. There is a need to improve accounting as a system of measuring economic phenomena and processes for a high level of ecological and economic management. The research is aimed at the development of theoretical and methodological approaches to accounting management for ecological quality of products based on the definition of the essence of the concept as an object of management under conditions of sustainable development, identification and systematization of factors of increasing the ecological quality of products and their management features, accounting identification of costs for ecological quality of products. According to the results of the research, it is established that the ecological quality of products is a combination of properties, which ensure excellent performance of assigned functions and the presence in products of those properties and characteristics that promote the maximum satisfaction of consumer needs and inquiries. The existing order of organization of accounting in Ukraine does not provide the provision of necessary information for the management of the ecological quality of products. The proposed directions of development of elements of the expense accounting method for the ecological quality of products will promote the expansion of information support for the adoption of substantiated and effective management decisions regarding the activities of business entities in accordance with the provisions of the concept of sustainable development.